Canal irrigation system rehabilitation and impact assessment - CHAUHAN1, MANOJ KUMAR; RAM, SHOBHA (Journal of Soil and Water Conservation, 2023)
In nature mostly the water resources and the agricultural lands with high production potentials are not found in proximity. Therefore, large volume of water is transported through irrigation canal to the areas having good agricultural potential. With passage of time the capacity of canals to control and carry the desired flow of water is dropped. In such conditions the supply of water canal system becomes short, irregular, and non-uniform. To remove these problems of old irrigation projects, the rehabilitation activities are planned and executed. For the rehabilitation activities heavy expenditure is made, therefore, after rehabilitation works it is imperative to assess the impact on the performance of the irrigation system. Indices namely, (i) Water Reach Ratio, (ii) Conveyance efficiency, (iii) Water delivery Index, (iv) Water Use Efficiency, (v) Reliability discharge Index, and (vi) Effectiveness of control structures Index for impact assessment of rehabilitation of canal irrigation systems have been proposed. These indices cover irrigation efficiencies, hydraulic changes which lower the performance of the canal system, water distribution aspects of canal system etc. A case study related to Ramial irrigation project of Odisha has been presented for the impact assessment of rehabilitation works on the performance of irrigation system.